A Longitudinal Investigation on the Reciprocal Relationship of Problematic Smartphone Use with Bedtime Procrastination, Sleep Quality, and Mental Health Among University Students - Cemei, Li; Sriram, Shyamkumar; Holý, Ondřej; Rehman, Shazia (Psychology research and behavior management, 2024)
BACKGROUND: Problematic smartphone use (PSU) is linked to various mental health issues, but the relationship between PSU, bedtime procrastination, and mental health symptoms is unclear. Sleep factors related to PSU and its mental health effects have been understudied. This study explores the longitudinal associations between PSU, bedtime procrastination, sleep quality, and mental health in university students. METHODS: In this study, a total of 683 university students participated by completing questionnaires on Smart Phone Addiction (SAS) scale, Bedtime Procrastination Scale (BPS), Pittsburgh Sleep Quality Index (PSQI), and Depression, Anxiety Stress Scales 21 (DASS-21) across two different time points with six-months interval between them. The participants were selected using a cluster sampling technique from Quaid-e-Azam University, Islamabad, Pakistan. A cross-lagged model was utilized to assess the longitudinal association between these variables. RESULTS: Statistically significant reciprocal associations were found between PSU, bedtime procrastination, and mental health symptoms. PSU at Time 1 significantly predicted PSU at Time 2, bedtime procrastination at Time 2, sleep quality at Time 2, and mental health symptoms at Time 2. Bedtime procrastination at Time 1 predicted PSU at Time 2, sleep quality at Time 2, and mental health symptoms at Time 2. Sleep quality at Time 1 predicted bedtime procrastination at Time 2 and mental health symptoms at Time 2. Mental health symptoms at Time 1 predicted PSU at Time 2 and sleep quality at Time 2. CONCLUSION: The research findings have significantly advanced understanding of the longitudinal connections between PSU, bedtime procrastination, sleep quality, and mental health indicators. This enhanced comprehension is instrumental for psychological practitioners in devising targeted interventions to mitigate such issues among the university student demographic.
Keywords: sleep quality; anxiety; bedtime procrastination; depression; problematic smartphone use; stress symptoms